Viśvanātha vāṅmaya sūcika - Vēṅkaṭarāmakōṭiśāstri, Kētavarapu, 1931- (Telugu Vibhāgamu, Snātakōttara Vidyā Kēndramu, 1974)
An index to the works of Vishwanath Satyanarayana, 1895-1976, Telugu litterateur.